Mathematical modeling to evaluate potato cultivation in high-andean soils using data analysis and the Runge Kutta method (Selecciones Matemáticas, 2024)
According to data collected by the International Potato Center (CIP) and the Departmental Federation of Peasant Communities (FEDECH), regarding the Huancavelica region. One of the most devastating diseases in the potato crop is ”Rancha”; scientifically known as Phytophtora infestan. Frog can be controlled by the application of fungicides, but due to the excessive growth of the population density of this pathogen produced by the frog fungus, it would be necessary to apply more fungicides, which poses a high environmental and  human health risk to those who consume this type of tuber in their diet. To measure the population growth of both species, a database will be built related to the percentage of potato crops per hectare that are attacked by this type of fungus. In this sense, a numerical mathematical model will be developed based on the Lotka-Volterra type differential equation system, which is solved with the Runge-Kutta RK2 and RK4 method, in order to contribute, in a non-invasive way, with an alternative for the prevention and control of this disease in potato crops in high Andean soils.
Keywords: Rancha fungus; environmental risk in potato crop; data cleaning; data analysis; Lotka- Volterra model; Runge-Kutta